In-depth analysis of large-scale screening of WRKY members based on genome-wide identification - Pan, Haoyu; Chen, Yu; Zhao, Jingyi; Huang, Jie; Shu, Nana; Deng, Hui; Song, Cheng (Frontiers in Genetics, 2023)
With the rapid advancement of high-throughput sequencing technology, it is now possible to identify individual gene families from genomes on a large scale in order to study their functions. WRKY transcription factors are a key class of regulators that regulate plant growth and abiotic stresses. Here, a total of 74 WRKY genes were identified from Dendrobium officinale Kimura et Migo genome. Based on the genome-wide analysis, an in-depth analysis of gene structure and conserved motif was performed. The phylogenetic analysis indicated that DoWRKYs could be classified into three main groups: I, II, and III, with group II divided into five subgroups: II-a, II-b, II-c, II-d, and II-e. The sequence alignment indicated that these WRKY transcriptional factors contained a highly conserved WRKYGQK heptapeptide. The localization analysis of chromosomes showed that WRKY genes were irregularly distributed across several chromosomes of D. officinale. These genes comprised diverse patterns in both number and species, and there were certain distinguishing motifs among subfamilies. Moreover, the phylogenetic tree and chromosomal location results indicated that DoWRKYs may have undergone a widespread genome duplication event. Based on an evaluation of expression profiles, we proposed that DoWRKY5, 54, 57, 21, etc. may be involved in the transcriptional regulation of the JA signaling pathway. These results provide a scientific reference for the study of DoWRKY family genes.